Progress in nucleic acid research and molecular biology. - Moldave, Kivie, 1923- (Progress in nucleic acid research and molecular biology ;, 2001)
Progress in Nucleic Acid Research and Molecular Biology provides a forum for discussion of new discoveries, approaches, and ideas in molecular biology. It contains contributions from leaders in their fields and abundant references.